Expectativas, metas y desempeño académico : un experimento de campo (2017)
"Recent studies show that goal setting encourages performance in a variety of contexts. Goals lead to a greater effort dedicated to a specific task, which ultimately show a better performance; particularly in employment and laboratory contexts. However, this result is ambiguous in academic contexts. This paper analyzes the effect of establishing a specific grade goal in a class test performance. Moreover, it is possible to analyze heterogeneous effects according to the gap in the established goals, measured as the difference between the expected grade and the student's goal. I design a field experiment where a sample of college students defines their expected grade in a test, and a random group additionally defines a goal in the same test. " -- Tomado del Formato de Documento de Grado.